Chapter Storie di strutture: note intorno a una lettera di Violante a Tabacco - PETRALIA, GIUSEPPE (Reti Medievali E-Book, 2021)
What are the limits of a history of structures? Can we aspire to a total or global history? In a letter to Giovanni Tabacco from 1980, discovered by Gian Maria Varanini, Cinzio Violante expressed his dissatisfactions as a historian, in a period in which he renewed his methodological ideas, with new research and broad summary visions. The problems of Violante and Tabacco are still relevant nowadays, while their dialogue is the sign of a generation united by a way of being historians that became the intellectual and moral commitment of entire existences.